Cost comparison between the construction of conventional method and interlocking block system - Nik Farahiyah , Nik Mohamed (2014)
IBS cost usually has many factors to affect it and some of it are swing of market demand, transportation cost, storage cost and so on. However, from the previous study, it is proven through questionnaire survey that lBS system is more effective to use compared to conventional method. The objectives for this study are to determine the cost for single, 2-storey and 3-storey house by using the conventional method, to determine the cost for single, 2-storey and 3-storey house by using the interlocking block system and to determine the most economic construction between conventional and interlocking block system in term of material, manpower and time. For this study, the calculation is used to determine the cost for single, 2-storey and 3-storey house from IBS system and conventional method. From the calculation, it performs a Bill of Quantity (BQ) for houses. The BQ shows the different cost and it is possible to choose which house is more economical in term of price. The result of this study shows that the cost for 1 storey house of the interlock block system is 23% less than conventional method. For 2 storey and 3 storey house, it is less 16% and 22% compared to conventional method. So from this result indicate that it is more efficient to use to construct house compare to conventional method. This is because it more economical in term of price. It also takes less time to construct the house and need fewer workers.